Pendampingan Program Berhenti Merokok pada Remaja di SMKS Kecamatan Padakembang Kabupaten Tasikmalaya - Dadi Hamdani; Andan Firmansyah; Elis Roslianti; Ade Fitriani; Henri Setiawan; Dedi Supriadi; Asep Gunawan; Fuzti Fauzia; Nur Hidayat; Suhanda Suhanda (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background: Deaths caused by smoking are very worrying, in the world as many as 225,700 people die from tobacco every year according to WHO in 2020 (Abdulateef, 2016; Alinaggar, 2011). Tobacco use in Indonesia aged over 15 years. It has increased again from the previous year, namely 28.96% (Alamsyah, 2017; Binita, 2016), and is still dominated by men at 7.14% Alamsyah, (21017). Smoking habits in teenagers due to misunderstanding of information, influence of advertising and influence of friends. In society, smoking is a measure of maturity level so teenage boys follow this behavior. The beginning of smoking behavior is caused by a community environment where the majority smoke and the invitation of friends to smoke (Huriyati, 2016; Izzati, 2016). Methods: participatory training and role-play are the methods used, starting from community formation, namely optimizing the role of cadres in the smoking cessation program. The next stage is education about smoking and training for administrators and cadres to stop smoking. The final stage is a follow-up to the smoking cessation program which will be carried out independently by cadres and evaluations carried out regularly by cadres. Results: Participants' knowledge about smoking was very diverse. During the activity, the participants had a high motivational interest. The enthusiasm of the counseling participants is a very good start to increasing insight. The level of knowledge of participants increased by up to 40% after the outreach activities were carried out. Conclusion: Providing counseling can increase students' knowledge about quitting smoking by 40% based on the results of the pre-test and post-test. The formation of a community smoking cessation program consisting of young students who volunteer to accompany their friends to quit smoking.